Experimental and numerical investigations on adhesively bonded tubular connections for moulded wooden tubes. (30th December 2019) - Hahn, Benjamin; Werner, Tom-Egmont; Haller, Peer
Highlights: Adhesive bonding of wooden tubes by injection. Real-scale tensile tests on thin-walled moulded wooden tubes. Probabilistic prediction of ultimate load capacity. Abstract: Moulded wooden tubes combine the advantages of the sustainable building material wood with the material efficiency that can be found in the field of steel and composite construction. They are particularly suitable for lightweight constructions and cantilevered structures under dynamic loads. The objective of ongoing research is the design of a joining solution that is appropriate for the material and structure of the tubes. This paper describes an adhesive approach for connecting thin-walled timber elements to tubular steel connectors. The presented solution will be applied for the fabrication of connections within a truss tower segment used in small wind power turbines. In addition to experimental investigations, numerical approaches to determine the load carrying capacity of such joints are presented. The experimental investigations include both compression and tensile tests on specimens of different sizes. For the numerical determination of the joint capacity a probabilistic approach is used which takes into account specific properties of brittle failure modes and allows for the determination of a characteristic strength value used by engineers in the design of structures. The numerical results are verified by the experimental data and show good accordance for both load cases.